Development of Low-Voltage Electrified Fish Guidance Racks for Safe Downstream Fish Migration - Moldenhauer-Roth, Anita; id_orcid:0 000-0002-2902-4028; Selz, Oliver M.; Unterberger, Felix; Albayrak, Ismail; id_orcid:0 000-0002-4613-6726; Boes, Robert; id_orcid:0 000-0002-0319-976X (International Association for Hydro-Environment Engineering and Research, 2022)
Downstream moving fish may have to pass through turbines or spillways of run-of-river hydropower plants (HPPs), which can result in life-threatening injuries. Fish guidance structures such as a vertical curved-bar rack (CBR) or horizontal bar rack (HBR) in combination with a bypass can safely guide different fish species around HPPs, thereby providing a safe downstream fish passage route. HBRs are a physical barrier to the passage of parts of the fish fauna due to narrow bar spacings and partly induce behavioral guidance, while the CBR creates turbulent structures in front of the rack, inducing a behavioral guidance and protection effect. HBRs are mainly applied at small- to medium-scale HPPs because of their velocity limitation and narrow bar spacing causing clogging problems. Combining an HBR with a low voltage electric field (e-HBR) may permit the use of larger bar spacings while maintaining high protection efficiencies. A CBR with a 50 mm bar spacing showed high protection rates for certain cyprinid species in laboratory experiments. However, European eel (Anguilla anguilla) were less receptive to hydraulic cues by the CBR resulting in low guidance efficiency. Electrifying the CBR (e-CBR) may improve the protection efficiency for eel. In the present study, the electric field generated at an e-HBR and e-CBR was numerically simulated. Subsequently, tests of e-HBR and e- BR were conducted with European eel in a large laboratory flume at ETH Zurich. Both e-HBR and e-CBR improved protection and guidance compared to the non – electrified racks for European eel. Guidance and protection efficiencies were not affected by the approach flow velocity varying from 0.15 m/s to 0.6 m/s.